2017
DOI: 10.1038/s41598-017-17057-y
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T follicular helper Cells Make a Difference in HIV Reservoir Size between Elite Controllers and Patients on Successful cART

Abstract: HIV latency is the main barrier to HIV eradication. Peripheral T follicular helper (pTfh) cells have a prominent role in HIV persistence. Herein, we analyzed the HIV reservoir size within memory CD4+ T-cell subsets in patients with HIV replication control. Twenty HIV-infected patients with suppressed HIV replication were included, with 10 elite controllers (EC) and 10 treated (TX) individuals. The HIV reservoir size was analyzed in resting memory CD4+ T-cells (Trm), pTfh, and non-pTfh cells using an ultrasensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Patients were recruited from four different hospitals in Madrid, Spain, during a period of 12 months. Inclusion criteria for HIV patients have been described elsewhere 47 . A group of 10 uninfected subjects were also included as control group (HC group).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients were recruited from four different hospitals in Madrid, Spain, during a period of 12 months. Inclusion criteria for HIV patients have been described elsewhere 47 . A group of 10 uninfected subjects were also included as control group (HC group).…”
Section: Methodsmentioning
confidence: 99%
“…Starting form fresh peripheral blood mononuclear cells (PBMCs), two different subsets of CD4 T-cells were purified: resting memory CD4 T (Trm) cells (defined as CD4+CD45RO+CD25−CD69−HLADR−) and peripheral T follicular helper (pTfh) cells (defined as CD4+ CD45RO+ CXCR5+). For this purpose, immunomagnetic separation was employed as has been described elsewhere 47 . Purity of each CD4 subset was tested by flow cytometry using a Sony Spectral flow cytometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed decline of cellassociated RNA may reflect the relative instability of effector cells, including PD-1+CD4+ T cells, which express viral proteins, or a decrease in the number of infectious virions that remain on FDCs within GC, thereby limiting new and preferential infection of Tfh [9]. In peripheral blood, Garcia et al reported no differences in HIV DNA concentrations between cells with a Tfh phenotype and those without a Tfh phenotype in either elite controllers or virologically suppressed individuals on ART [21]. Whether peripheral blood cells with a Tfh phenotype truly reflect lymphoid tissue Tfh has not been firmly established, although a clonal relationship was recently reported between these subsets [22**].…”
Section: Role Of Follicular T Cells In Hiv Infection Replication Anmentioning
confidence: 99%
“…Boritz and colleagues studied the persistence of virus in HIV controllers and found that, despite effective antiviral immune responses in these individuals, their reservoir was maintained through viral replication, clonal expansion of latently infected cells, and a low level of circulating infected cells 57 . However, it was recently demonstrated that the HIV reservoir is smaller in elite controllers, particularly in peripheral T follicular helper cells, meaning the host response within these controllers is able to limit the HIV reservoir size 58 . The HIV reservoir found in lymphoid tissue is a major barrier to current CD8 T-cell-based cure efforts because without effective immune responses or daily ART, these latently infected cells reactivate and virus rebounds.…”
Section: Future Directionsmentioning
confidence: 99%